Transformation of Abimanyu’s Character in Serat Wirawiyata - Hery Riyanto (Pusat Unggulan Ipteks Javanologi Universitas Sebelas Maret, 2025)
Serat as a literary work has its own uniqueness. Authors often transform or adapt stories in their writing. One of the literary works that contains transformation is Serat Wirawiyata. Serat Wirawiyata is a work of Mangkunegara IV which contains the teachings of warriors in which transforms the character Abimanyu to be used as a role model. This research is qualitative research with interpretative-descriptive research method. The type of research is library research. The theories used in this research are literary reception theory and intertextual. Primary data in this research is the transformation of Abimanyu’s character in Serat Wirawiyata while secondary data in this research includes data obtained from books, articles, and documents related to the research. The result of this research is that in Serat Wirawiyata there is a transformation of Abimanyu character, the intention of the transformation of Abimanyu character is in order to change the concept of darma into karma with the aim as a teaching material for soldiers in carrying out their duties and obligations.